DIFFERENT IDEOLOGIES OF RURAL DEVELOPMENT - Tiwari, Archana (International Journal of Research -GRANTHAALAYAH, 2017)
In the context of India, the Sanatan-Puranic concept has been that India is a country of villages whose basis of economic-social attainment is agriculture, as is evident from the following verses. "As Shudra Janpraya, prosperous agriculture Kshetropa Yoga Bhumadhya, Vasati Gram Anusika. "1 In the Markandeya Purana of mythological Sanskrit literature, the above reference has been made in the context of the village. It is said in the specialty of the village - where the agricultural work is done and where the agricultural sector is grouped, it is the village. The rise of the village is associated with the rise of the agricultural economy in history. Due to the invention of the plow (Bnsjjp Anjawat), man was able to develop agriculture permanently, which is the basic source of the system of food grains. Rural development generally refers to the process of improving the standard of living associated with the economic well-being of people living in relatively isolated and sparsely populated areas. Scholars have given the definitions of rural development as follows - Literally defining rural development means the all-round development of rural. Development that can lead to physical and mental development of the people there. भारत के संदर्भ में सनातन-पुरातन अवधारणा रही है कि भारत गाँवों का देश है जिसकी आर्थिक-सामाजिक प्राप्ति का आधार कृषि है, जैसा कि निम्नांकित श्लोक से स्पष्ट होता है। ‘‘यथा शूद्र जनप्राय, समृद्ध कृषिकला क्षेत्रोप योग भूमध्र्य, वसति ग्राम संज्ञिका।’’1 पौराणिक संस्कृत साहित्य के मार्कण्डेय पुराण में, ग्राम के संदर्भ में उक्त उल्लेख आया है। गाँव की विशेषता में कहा गया - जहाँ कृषि कार्य किया जाता है एवं जहाँ कृषि क्षेत्र समूह है वह गाँव है। गाँव का उदय, इतिहास के कृषि अर्थव्यवस्था के उदय के साथ जुड़ा है। हल (ब्नसजपअंजवत) के अविष्कार के कारण ही मनुष्य स्थायी रूप से कृषि का विकास कर पाया जोकि खाद्यान्न की व्यवस्था का मूल स्रोत है। ग्रामीण विकास आम तौर पर अपेक्षाकृत पृथक व कम आबादी वाले क्षेत्रों में रहने वाले लोगों की आर्थिक खुशहाली से संबद्ध जीवन स्तर में सुधार की प्रक्रिया को दर्शाता है।2 विद्वानों ने ग्रामीण विकास की परिभाषायें निम्न प्रकार दी हैं - ग्रामीण विकास को शाब्दिक रूप में परिभाषित करने का अर्थ है - ग्रामीण का चहुँमुखी विकास। वह विकास जिससे वहां की जनता का शारीरिक एवं मानसिक विकास हो सके।